Effects of one minute and ten minutes of walking activity in rats with arthritis induced by complete Freund's adjuvant on pain and edema symptoms - Gomes R.P.* (2014)
This study evaluated the effects of two protocols of exercise on nociception, edema and cell migration in rats with CFA-induced arthritis. Female Wistar rats (200- 250g, n = 50) was monoarthritis-induced by complete Freund's adjuvant (CFA; Mycobacterium butyricum, 0.5mg/mL; 50μL) into the right knee joint (TF; n = 24) or right ankle joint (TT; n = 26). Incapacitation was measured by the paw elevation time (TEP; s) in 1-min periods of observation. The edema of the knee or ankle joints was evaluated by the variation of the articular diameter (DA, cm) and by the paw volume variation (EP, mL), respectively. Both were measured during 10 consecutive days. Two protocols of exercise were performed: (a) in the constant exercise group (TF, n = 6; TT, n = 6) performing 1 minute of daily exercise on the cylinder; (b) variable exercise group (TF, n = 6; TT, n = 7), the exercise increased by 1 minute per day. The control groups (TF, n = 12; TT, n = 13) didńt perform the exercise. After 10 days, the animals were euthanized for total (CT; cells/mm3) and differential leukocyte counts (mononuclear- MON, and polymorphonuclear- PMN, cells/mm3) of the articular inflammatory exudate. The variable exercise protocol inhibited incapacitation and edema for both joints. However, cell migration decreased only in the TF. The constant exercise reduced edema in both joints, and cell migration was decreased in the TT. However, the incapacitation was not reduced. Variable exercise seemed to be more effective in reducing the inflammatory parameters than constant exercise. © 2014 Elsevier Editora Ltda.